Break My Soul (please don’t). The event of the Great Resignation and the politics of affectivity - Valls Boix, Juan Evaristo (LABOS Revista de Derecho del Trabajo y Protección Social, 2024)
The aim of this paper is to analyze the political scope of the Great Resignation as a social event. Despite the widespread tendency to relativize the importance of this phenomenon, this article argues for the value of the Great Resignation as an affective revolution and resistance against the emotional exploitation and the government of desire that characterize work and productivity in neoliberal societies. It argues that this event articulates a post-capitalist desire (Fisher) or a withdrawal of desire (Berardi) that is at the basis of a new affective politics and a non-neoliberal subjectivity, which The New York Times has called “anti-ambition”. The emergence of a new sensibility is developed through other events such as the feminist strikes or the Chinese Tan Ping movement, a constellation of protests and activisms that account for a social movement towards a politicization of disconfort and the invention of a way of life beyond its design, not colonized by work. Medium passions such as placidity, laziness and calm become key in this new grammar of care post-capitalist desire.